Didactic game for 5-6 years old children’s cognitive development - Buboviča, Jana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article raised in 5-6 year-old children's cognitive development process and contributing factors. Emphasizes the didactic essence of the game and the importance of a child's life activities. It describes the structure and benefits of the child during the game. Target for updating the didactic significance of the game for 5-6 years old children's cognitive development in order to obtain a practical study, affirmative or negative information.A study conducted by demonstrating the usefulness of didactic games the child's cognitive development, for example, 69.3% of girls and 60.2% boys have mastered the ability to observe and explore, show curiosity and a desire to solve problems, demonstrate constructive thinking.